"Collaborators" or "Resistors, " "Loyalists" versus "Rebels": Problematizing Colonial Binary Nomenclatures through the Prism of Dedan Kimathi's Career. (1st July 2018) - Githuku, Nicholas
Abstract : This paper evaluates the "evolution" of African anti-imperial resistance in African history in general and that of Kenya in particular, in the attempt to reveal hidden or private/public transcripts and inherent power dynamics that fueled political dissent, opposition, and action. James C. Scott informs us that people, generally, and especially where relations of power are concerned, do not usually wear their opinions, emotions, motives or deepest thoughts that shape their behavior on their sleeve. Therefore, throughout history, the vast majority of people, the "dissembled weak, " or "those subject to elaborate and systematic forms of social subordination, " are given to putting up "public performances, " a perfunctory adherence to imposed laws, policies, and the status quo as is required of them. The outcome of this general rule of thumb is a "public transcript" that, "by its accommodationist tone, " provides "convincing evidence for the hegemony of dominant values, for the hegemony of dominant discourse." Such public transcripts are misleading since they lead observers to "conclude that subordinate groups endorse the terms of their subordination and are willing, even enthusiastic, partners in that subordination." The implications of Scott's insightful paradigmatic conceptualization of the internal dynamics of the "arts of resistance" are far-reaching. This radical conceptualization of the concealed roots of external human behavior, and "public performances, " naturally complicates earlier analysis of social categories of African responses to European imperialism thought to be straightforward and concrete or mutually exclusive. It presents a possibility for an analysis and reinterpretation of the deep psychosociological springs and triggers of human behavior, which necessitates a crucial return to this important theme in African history. That is, a more nuanced scrutiny and critical study of the popular mind or populist reason. This paper is such a critical reexamination of problematic social categories and Eurocentric binary nomenclatures.